SON-1010: an albumin-binding IL-12 fusion protein that improves cytokine half-life, targets tumors, and enhances therapeutic efficacy - Cini, John K.; Kenney, Richard T.; Dexter, Susan; McAndrew, Stephen J.; Eraslan, Rukiye-Nazan; Brody, Rich; Rezac, Darrel J.; Boohaker, Rebecca; Lapi, Suzanne E.; Mohan, Pankaj (Frontiers in Immunology, 2024)
BackgroundCytokines have been promising cancer immunotherapeutics for decades, yet only two are licensed to date. Interleukin-12 (IL-12) is a potent regulator of cell-mediated immunity that activates NK cells and interferon-γ (IFNγ) production. It plays a central role in multiple pathways that can enhance cancer cell death and modify the tumor microenvironment (TME). Attempts to dose rIL-12 were initially successful but IFNγ toxicity in Phase 2 complicated further development in the late 1990s. Since then, better dosing strategies have been developed, but none have achieved the level of cancer control seen in preclinical models. We set out to develop a novel strategy to deliver fully functional IL-12 and other biologics to the TME by binding albumin, taking advantage of its ability to be concentrated and retained in the tumor.MethodsSingle-chain variable fragments (scFv) were identified from a human phage display library that bound human, mouse, and cynomolgus macaque serum albumin, both at physiologic and acidic conditions. These were taken through a series of steps to identify strongly binding molecules that don’t interfere with the normal physiology of albumin to bind FcRn, giving it prolonged half-life in serum, along with SPARC/GP60, which allows albumin to target the TME. A final molecule was chosen and a single mutation was made that minimizes the potential for immunogenicity. This fully human albumin-binding (FHAB®) domain was characterized and manufacturing processes were developed to bring the first drug candidate into the clinic.ResultsOnce identified, the murine form of mIL12-FHAB was studied preclinically to understand its mechanism of action and biodistribution. It was found to be much more efficient at blocking tumor growth compared to murine IL-12, while stimulating significant IFNγ production with minimal toxicity. SON-1010, which uses the human IL-12 sequence, passed through all of the characterization and required toxicology and is currently being studied in the clinic.ConclusionsWe identified and developed a platform technology with prolonged half-life that can target IL-12 and other immune modulators to the TME. Safety and efficacy are being studied using SON-1010 as monotherapy and in combination with checkpoint blockade strategies.